(untitled) (MAUSAM, 2005)
With the discovery of a dipole in Indian Ocean Sea Surface Temperature (SST), the Indian Ocean has been gaining an increasing importance in the context of global climate. SST is one of the important oceanic parameters controlling the ocean climate. In view of this importance, an attempt has been made in this study to examine the inter-annual and inter-seasonal variability of SST over (i) Equatorial Indian Ocean (5° N - 5° S and 50° E - 100° E) and (ii) North Indian Ocean (5° N - 20° N and 50° E - 100° E), during the period 1961-98. The values of seasonal SST anomaly over these sectors of Indian Ocean are computed for the four standard meteorological seasons over India, viz., Winter (January - February), Pre-monsoon (March - May), SW Monsoon (June - September) and Post-Monsoon (October - December). The variability of seasonal SST anomaly is examined, using various standard statistical methods and procedures, on inter-annual as well as decadal time-scale and the results are inter-compared. The SST anomaly over both the above sectors of Indian Ocean, for all the four seasons, shows an increasing trend during 1961-98, more particularly and prominently, after mid-1970s.